Hubungan Antara Status Gizi (Stunting dan Tidak Stunting) dengan Kemampuan Kognitif Remaja di Kabupaten Sukoharjo, Jawa Tengah - Rahmaningrum, Zella Novi, dr. M. Shoim Dasuki, M.Kes (2017)
Adolescence is the period of human growth, a time of critical transition in the life span at a tremendous pace in growth and change, both physical and psychosocial. Stunting is the result of chronic or recurrent malnutrition. Prelavence stunting in adolescents aged 13-15 years is 35,1%. Nervous system perfomance of stunted children usually decrease that can impact to cognitive ability. This research is an analytic observational study with case control approach, it is carried out in Muhammadiyah 1 Kartasura junior high school. Respondents that used each 26 samples for both good and less cognitive ability selected using purposive sampling techniques. Nutritional status measured by Height for Age (HAZ) and cognitive function by Standard Progressive Matrices (SPM). Data analysis used chi-square test. The results showed that 12 people stunted, 11 people of them had a less cognitive ability. Whereas 40 people non-stunted, 25 people of them had a good cognitive ability. Stunting as a risk factor that could affect cognitive abilities with p-value 0,001 (<0,05) and odds ratio (OR) 18,333. The conclusion is there is a significant correlation between stunting and cognitive ability in Muhammadiyah 1 Kartasura junior high school, Sukoharjo. Stunted adolescents had low cognitive ability less 18,333 times greater than non-stunted